Diabetes Mellitus in Children with Acute Recurrent and Chronic Pancreatitis: Data From the INternational Study Group of Pediatric Pancreatitis. Issue 5 (November 2019) - Bellin, Melena D.; Lowe, Mark; Zimmerman, M. Bridget; Wilschanski, Michael; Werlin, Steven; Troendle, David M.; Shah, Uzma; Schwarzenberg, Sarah J.; Pohl, John F.; Perito, Emily; Ooi, Chee Yee; Nathan, Jaimie D.; et al.
ABSTRACT: Objectives: Adults with chronic pancreatitis (CP) have a high risk for developing pancreatogenic diabetes mellitus (DM), but little is known regarding potential risk factors for DM in children with acute recurrent pancreatitis (ARP) or CP. We compared demographic and clinical features of children with ARP or CP, with and without DM, in the INternational Study Group of Pediatric Pancreatitis: In Search for a CuRE (INSPPIRE) registry. Methods: We reviewed the INSPPIRE database for the presence or absence of physician-diagnosed DM in 397 children, excluding those with total pancreatectomy with islet autotransplantation, enrolled from August 2012 to August 2017. Patient demographics, BMI percentile, age at disease onset, disease risk factors, disease burden, and treatments were compared between children with DM (n = 24) and without DM (n = 373). Results: Twenty-four children (6% of the cohort) had a diagnosis of DM. Five of 13 tested were positive for beta cell autoantibodies. The DM group was 4.2 years [95% confidence interval (CI) 3–5.4] older at first episode of acute pancreatitis, and tended to more often have hypertriglyceridemia [odds ratio (OR) 5.21 (1.33–17.05)], coexisting autoimmune disease [OR 3.94 (0.88–13.65)] or pancreatic atrophy [OR 3.64 (1.13, 11.59)]. Conclusion: Pancreatic atrophy may be more common among children with DM, suggesting more advanced exocrine disease. However, data in this exploratory cohort also suggest increased autoimmunity and hypertriglyceridemia in children with DM, suggesting that risk factors for type 1 and type 2 DM, respectively may play a role in mediating DM development in children with pancreatitis.